The Implementation of Green English Language Teaching Writing Skill in Secondary School: A Survey Research - Mardyansah, Achmad Fahrizza; Setiawan, Slamet; Nugroho, Him'mawan Adi (Electronic Journal of Education, Social Economics and Technology, 2025)
Green English language teaching is driven by the idea that, given its global scope, English language teaching (ELT) should not only equip students with language skills, but also enhance their knowledge of important global issues. However, because it shapes how we as humans view and interact with the natural world, the eco-pedagogical significance of the green materials in ELT textbooks has an impact on how nature is portrayed linguistically and discursively, as well as how humans and nature interact. This project aims to investigate students' writing skills around the environment which shows that students' writing skills are improving and the implementation of green English language teaching is good. The researcher distributed survey questionnaires and conducted interviews with the respondents.  Then, the findings of this study showed that most of the students had positive perceptions in green English language teaching to improve their writing and English language skills. Although, some of them have negative perceptions in some parts of green English language teaching to improve English writing and language skills. In addition, green english language teaching is very useful and helpful in fostering awareness towards students to be more confident when expressing writing ideas and suggestions.